1998
DOI: 10.1002/(sici)1521-4141(199806)28:06<1867::aid-immu1867>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

The antigen presentation pathway in medullary thymic epithelial cells, but not that in cortical thymic epithelial cells, conforms to the endocytic pathway

Abstract: Murine medullary thymic epithelial cells (mTEC), but not cortical thymic epithelial cells (cTEC), are able to present a soluble antigen, ovalbumin, to helper T cells (Mizuochi, T. et al., J. Exp. Med. 1992. 175: 1601-1605). This functional difference between the mTEC and the cTEC is particularly important when we consider the thymic selection of the T cell repertoire. In the previous report, we proposed that mTEC and cTEC utilize two distinct antigen processing/presenting pathways (Kasai, M. et al., Eur. J. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Peptide elution experiments utilizing purified B cells from DO-KO and DO-wild-type (DO-WT) mice were performed. We justified the use of B cells instead of mTECs for two main reasons: (1) the technical limitation of obtaining enough mTECS to attain reliable results and (2) the known similarities in expression of MHC class II molecules, DM, and cathepsins, the main components of the antigen processing machinery in mTECs [30][31][32][33][34][35], along with DO [8,36]. Analyses of two independent experiments (each comprising pools of 5 or 10 mice per group) showed that nearly 90% of eluted peptides were shared between the two strains, and 10% were unique peptides.…”
Section: Do-ko B Cells Present Peptides Of Lower Kinetic Stabilitymentioning
confidence: 99%
“…Peptide elution experiments utilizing purified B cells from DO-KO and DO-wild-type (DO-WT) mice were performed. We justified the use of B cells instead of mTECs for two main reasons: (1) the technical limitation of obtaining enough mTECS to attain reliable results and (2) the known similarities in expression of MHC class II molecules, DM, and cathepsins, the main components of the antigen processing machinery in mTECs [30][31][32][33][34][35], along with DO [8,36]. Analyses of two independent experiments (each comprising pools of 5 or 10 mice per group) showed that nearly 90% of eluted peptides were shared between the two strains, and 10% were unique peptides.…”
Section: Do-ko B Cells Present Peptides Of Lower Kinetic Stabilitymentioning
confidence: 99%
“…Both APCs and mTECs present exogenous antigens on MHC II via the endocytic pathway, although APCs are more efficient. For the presentation of intracellular peptides APCs, cTECs and mTECs use the constitutive secretory pathway and the lysosomal pathway via autophagy 49 , 50 . The role of autophagy in these selection processes during T‐cell maturation will be described here.…”
Section: Autophagy In Thymocyte Developmentmentioning
confidence: 99%
“…Cathepsin S activity (B) and SDS-stable MHCII ab dimer level (C) were analyzed. Three independent experiments were performed, and the average enzyme activity and signal intensity are shown, with error bars indicating of Infectious Diseases) (Kasai et al, 1998 and. GM-CSFproducing CHO cells were from Dr. Sudo (Toray).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%